Best Practices for Intrathecal Baclofen Therapy: Troubleshooting. Issue 6 (19th July 2016) - Saulino, Michael; Anderson, David J.; Doble, Jennifer; Farid, Reza; Gul, Fatma; Konrad, Peter; Boster, Aaron L.
Abstract : Introduction: Troubleshooting helps optimize intrathecal baclofen (ITB) therapy in cases of underdose, overdose, and infection. Methods: An expert panel of 21 multidisciplinary physicians currently managing >3200 ITB patients was convened, and using standard methodologies for guideline development, created an organized approach to troubleshooting ITB. They conducted a structured literature search that identified 263 peer‐reviewed papers, and used results from an online survey of 42 physicians currently managing at least 25 ITB patients each. Results: The panel developed two algorithms. The first was for loss‐of‐efficacy and applies to patients with previously well‐controlled hypertonia on a stable dosing regimen who have increased spasticity Evaluation includes a targeted history (onset, duration, course, exacerbating/relieving factors, medications, recent procedures), physical examination (neuromuscular, vital signs, mental status), radiologic/laboratory testing (catheter imaging, noxious stimuli, infection, rising CK levels), and pump telemetry (pump interrogation, reservoir volume). Rapidly progressing hypertonia with autonomic instability or hypotonia and somnolence require emergent care and perhaps hospitalization. The second algorithm was for emergent care and describes treatment of overdose or withdrawal, which requires immediate care in a monitored setting and restoration of ITB delivery. The previous dosing schedule can be used in withdrawal of short duration; 10–20 mg every six hours can be used in longer‐duration withdrawal. Supportive care includes maintenance of airway, respiration, and circulation. Seizure prevention should be considered, along with pump reprogramming or interruption, cerebrospinal fluid drainage, and sequential lumbar punctures/drains. Physostigmine and flumazenil are not usually advised. Superficial infections can be treated with oral antibiotics, and deep infections with broad‐spectrum IV antibiotics (e.g., cefazolin, clindamycin, vancomycin). Explantation is often required. A new pump can be implanted in a new site under IV antibiotic coverage. Conclusions: Orderly troubleshooting helps ensure patient safety.